Perceiving Music Through the Lens of Synaesthesia and Absolute Pitch. (August 2021) - Glasser, Solange
Synaesthesia and absolute pitch (AP) are two rare conditions that occur more frequently within populations of artistic professionals. Current thinking surrounding synaesthesia and AP and their relationship to music perception form the focus of this article. Given that synaesthesia has rarely been discussed in the music literature, the article surveys and consolidates general neurobiological, psychological, and behavioural evidence to summarise what is currently known on this topic, in order to link this back to the conditions that most relate to music. In contrast, research on AP is now well established in the music literature, but the important gap of linking AP to other conditions such as synaesthesia has yet to be fully explored. This article investigates the potential relationship between synaesthesia and AP for musicians who possess both conditions by systematically comparing the definitions, classifications, prevalence, diagnoses, and impacts on music perception of synaesthesia and AP and provides insights into the varying states of the literature and knowledge of both conditions. In so doing, this article aims to facilitate a greater understanding of music and auditory forms of synaesthesia and their interaction with AP and encourage increased research effort on this important topic.